2017
DOI: 10.4490/algae.2017.32.9.9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two phototropins in the freshwater green alga, Spirogyra varians (Streptophyta, Zygnematales)

Abstract: Freshwater algae living in shallow waters have evolved various photomovement to stay in the optimum light condition for survival. Previous action-spectra investigations showed that Spirogyra filaments have phototropic movement in blue light. To decipher the genetic control of phototropic movement, two phototropin homologues were isolated from Spirogyra varians, and named SvphotA and SvphotB. Both phototropins have similar molecular structure consisted of two light-oxygen-voltage domains (LOV1, LOV2) and a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Current investigations revealed that Klebsormidium contains phototropins [54] and its genome has acquired genes (some of them similar to land plants) which allow specific adaptation to terrestrial life by providing protection against the detrimental effects of high-intensity light [55]. These results are in accordance with the suggested gradual colonization of land habitats by descendents of streptophyte algae, for which the major advantage was the physiological preadaptation to terrestrial existence by their primary freshwater life style [56].…”
Section: Introductionsupporting
confidence: 52%
“…Current investigations revealed that Klebsormidium contains phototropins [54] and its genome has acquired genes (some of them similar to land plants) which allow specific adaptation to terrestrial life by providing protection against the detrimental effects of high-intensity light [55]. These results are in accordance with the suggested gradual colonization of land habitats by descendents of streptophyte algae, for which the major advantage was the physiological preadaptation to terrestrial existence by their primary freshwater life style [56].…”
Section: Introductionsupporting
confidence: 52%
“…). We could not find any neochrome homologues in the S. varians transcriptome (Lee and Kim ). At the moment, little is known of the regulation pathway and machineries of red/far‐red light movement in freshwater algae even in the Mougeotia model (Banaś et al.…”
Section: Discussionmentioning
confidence: 84%
“…A neochrome gene which contains both phytochrome and phototropin domains has been found in M. scalaris, but the involvement of this chimeric photoreceptor in the chloroplast movement has not been demonstrated (Suetsugu et al 2005). We could not find any neochrome homologues in the S. varians transcriptome (Lee and Kim 2017a). At the moment, little is known of the regulation pathway and machineries of red/far-red light movement in freshwater algae even in the Mougeotia model (Bana s et al 2012).…”
Section: Phytochromes In Spirogyra Variansmentioning
confidence: 76%
See 2 more Smart Citations